Culture, Institutions & the Long Divergence - Alberto Bisin; Jared Rubin; Avner Seror; Thierry Verdier (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Recent theories of the Long Divergence between Middle Eastern and Western European economies focus on Middle Eastern (over-)reliance on religious legitimacy, use of slave soldiers, and persistence of restrictive proscriptions of religious (Islamic) law. These theories take as exogenous the cultural values that complement the prevailing institutions. As a result, they miss the role of cultural values in either supporting the persistence of or inducing change in the economic and institutional environment. In this paper, we address these issues by modeling the joint evolution of institutions and culture. In doing so, we place the various hypotheses of economic divergence into one, unifying framework. We highlight the role that cultural transmission plays in reinforcing institutional evolution toward either theocratic or secular states. We extend the model to shed light on political decentralization and technological change in the two regions.
Keywords: O10; P16; P48; N34; N35; Z12; O33; 330; long divergence; cultural transmission; institutions; legitimacy; religion